2, 5-Dihydroxy-4-methoxybenzophenone: a novel major in vitro metabolite of benzophenone-3 formed by rat and human liver microsomes. (June 2013) - Kamikyouden, Nagisa; Sugihara, Kazumi; Watanabe, Yoko; Uramaru, Naoto; Murahashi, Tsuyoshi; Kuroyanagi, Masanori; Sanoh, Seigo; Ohta, Shigeru; Kitamura, Shigeyuki
<x xml:space="preserve">Abstract</x> 1. When benzophenone-3 (2-hydroxy-4-methoxybenzophenone; BP-3) was incubated with liver microsomes of untreated rats in the presence of NADPH, the 5-hydroxylated metabolite, 2, 5-dihydroxy-4-methoxybenzophenone (5-OH-BP-3), was formed as a major novel metabolite of BP-3. The 4-desmethylated metabolite, 2, 4-dihydroxybenzophenone (2, 4-diOH-BP), previously reported as the major in vivo metabolite of BP-3, was also detected. However, the amount of 5-OH-BP-3 formed in vitro was about the same as that of 2, 4-diOH-BP. 2. The oxidase activity affording 5-OH-BP-3 was inhibited by SKF 525-A and ketoconazole, and partly by quinidine and sulfaphenazole. The oxidase activity affording 2, 4-diOH-BP was inhibited by SKF 525-A, ketoconazole and α-naphthoflavone, and partly by sulfaphenazole. 3. The oxidase activity affording 5-OH-BP-3 was enhanced in liver microsomes of dexamethasone-, phenobarbital- and 3-methylcholanthrene-treated rats. The activity affording 2, 4-diOH-BP was enhanced in liver microsomes of 3-methylcholanthrene- and phenobarbital-treated rats. 4. When examined recombinant rat cytochrome P450 isoforms catalyzing the metabolism of BP-3, 5-hydroxylation was catalyzed by P450 3A2, 1A1, 2B1, 2C6 and 2D1, while 4-desmethylation was catalyzed by P450 2C6 and 1A1.